Mobilities, aesthetics and civic engagement: Getting at-risk youth to look at their communities. (1st June 2016) - Pariser, David; Castro, Juan Carlos; Lalonde, Martin
This article describes a mobile media art curriculum for engaging at-risk students with their schooling and with civic engagement. The pilot study was conducted with at-risk youth who were seeking their high school diplomas. The curriculum encouraged participants to use mobile media in school and outside. Students examined aspects of their neighbourhoods and sometimes explored themes suggested by the workshop leader. Data consisted of participants' images, their posts and interview responses. We noted that civic engagement grew out of participants' initial interest in, and concern for, the formal, technical and aesthetic aspects of their images. Our participants recognized that, if an image is well made, it will be that much more effective in communicating its civic message. In this article, we will consider the primacy of the aesthetic as a promising principle for developing curricula that reorient at-risk youth.